On the Horadam sequence of order three - Amrouche, S.; Belbachir, H.; Cesarano, C.; Ricci, P.E. (Karpats'kì matematinì publìkacìï, 2025)
In this paper, we define a generalized Horadam triangle in which the sum of elements located along the diagonal lines corresponds to the terms of generalized Horadam sequence of order three. We establish a relation between generalized Horadam triangle and the generalized Delannoy triangle. Additionally, we define the $q$-analogue of the generalized Tribonacci sequence and generalized Horadam sequence of order three. У цій статті ми визначаємо узагальнений трикутник Горадама, в якому сума елементів, розташованих уздовж діагональних ліній, відповідає членам узагальненої послідовності Горадама третього порядку. Встановлено зв'язок між узагальненим трикутником Горадама та узагальненим трикутником Делануа. Крім того, ми визначаємо $q$-аналог узагальненої послідовності трібоначчі та узагальненої послідовності Горадама третього порядку.